The interplay between serine proteases and caspase-1 regulates the autophagy-mediated secretion of Interleukin-1 beta in human neutrophils - Keitelman, Irene A.; Shiromizu, Carolina M.; Zgajnar, Nadia R.; Danielián, Silvia; Jancic, Carolina C.; Martí, Marcelo A.; Fuentes, Federico; Yancoski, Judith; Vera Aguilar, Douglas; Rosso, David A.; Goris, Verónica; Buda, Guadalupe; et al. (Frontiers in Immunology, 2022)
Neutrophils play major roles against bacteria and fungi infections not only due to their microbicide properties but also because they release mediators like Interleukin-1 beta (IL-1β) that contribute to orchestrate the inflammatory response. This cytokine is a leaderless protein synthesized in the cytoplasm as a precursor (pro-IL-1β) that is proteolytically processed to its active isoform and released from human neutrophils by secretory autophagy. In most myeloid cells, pro-IL-1β is processed by caspase-1 upon inflammasome activation. Here we employed neutrophils from both healthy donors and patients with a gain-of-function (GOF) NLRP3-mutation to dissect IL-1β processing in these cells. We found that although caspase-1 is required for IL-1β secretion, it undergoes rapid inactivation, and instead, neutrophil serine proteases play a key role in pro-IL-1β processing. Our findings bring to light distinctive features of the regulation of caspase-1 activity in human neutrophils and reveal new molecular mechanisms that control human neutrophil IL-1β secretion.